Ascenso Ferreira: um poeta-cantador da cultura pernambucana - Ramos, Joranaide Alves (2013)
This study examines the work Catimbó, written by Ascenso Ferreira (1895-1965), seeing it, especially as a poetic expression of the northeast popular culture, observing the affinities that the poetic diction of this pernambucano author remained with the modernists precepts of the 1922 Modern Art Week. The first chapter describes the cultural environment in Recife, noticing some socio-economic aspects that marked the region; examines the way the paulista modernism arrives to Pernambuco and, simultaneously, the intensification of regionalist´s ideas. Still in this first chapter, we begin the reading of poems ("Desespero", "A casa-grande de Megaípe", "Noturno", "O Samba", "História pátria", "Catimbó", "Minha terra", "Dor" and "Sertão") by Ascenso Ferreira, showing how the Pernambucana culture is poetized by the author of Catimbó. In the second chapter we considered Ascenso Ferreira as a regionalist-modernist poet, showing how the pernambucano has joined the stylistic innovation of modernism to the recovery of the traditions of his land, through the poems "Os engenhos da minha terra", "Tradição", "Vamos embora, Maria", "Quadrilha de Caetano Norato", "A pega do boi", "A rua do rio", "Graf Zeppelin", "O meu poema de São Francisco" and "Oropa, França e Bahia". In the third chapter, we point to Catimbó as a book thematically linked especially to popular culture, presenting the reading of poems of this book that deal poetically with the nordestinidade ascensiana through verses which reveal the cultural components of his land and its people, as "A cavalhada", "Carnaval do Recife", "Meu carnaval", "Senhor São João", "Natal", "Mês de Maio", "Reisado", "Bumba-meu-boi" and "Maracatu".